2019
DOI: 10.1371/journal.pone.0226127
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of tuberculosis and HIV co-infection in Ethiopia

Abstract: BackgroundTuberculosis (TB) and human immunodeficiency virus (HIV) are the leading causes of infectious-disease-related deaths in Ethiopia, but little is known about their spatial distribution across the country. The aim of this study was to investigate the spatial patterns of TB and HIV co-infection in Ethiopia at the district level.MethodsWe conducted an ecological study using TB and HIV data reported from all regions of Ethiopia through the national Health Management Information System (HMIS), between June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
54
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 33 publications
13
54
1
8
Order By: Relevance
“…The high HIV co-infection across all districts maybe driving the TB epidemic. However, despite a similar average HIV prevalence, there were differences in TB prevalence, (cases per capita) by district and also spatial distribution suggesting that HIV alone was not the cause of the observed TB distribution as reported from a study from Ethiopia [26].…”
Section: Plos Onementioning
confidence: 47%
See 1 more Smart Citation
“…The high HIV co-infection across all districts maybe driving the TB epidemic. However, despite a similar average HIV prevalence, there were differences in TB prevalence, (cases per capita) by district and also spatial distribution suggesting that HIV alone was not the cause of the observed TB distribution as reported from a study from Ethiopia [26].…”
Section: Plos Onementioning
confidence: 47%
“…Studies from China and Ethiopia also reported that low access to health care services was associated with increased number of TB cases. [26,33].…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies conducted in Ethiopia have shown a substantial geographical variation of TB incidence at district level. [6][7][8][9] Such small-area variations of TB may have important implications for local and national health policy in that policymakers, clinicians and public health professionals might benefit from evidence to target interventions to those areas and communities at the highest risk. However, previous spatial analyses of TB have been generally conducted using routinely collected TB notification data.…”
Section: Introductionmentioning
confidence: 99%
“…En relación al grupo de edad, se observó que la coinfección afecta a personas de 25 a 44 años, que viven en el área urbana. El perfil de coinfección ha ido cambiando en Brasil, a pesar de la alta prevalencia en las regiones sur y sureste, las tasas de incidencia han aumentado en las regiones norte y noreste, con un predominio de casos en pacientes de 25 a 59 años que viven en la zona urbana, un hecho asociado con el estilo de vida de los adultos jóvenes a menudo vinculado a la falta de conciencia de su vulnerabilidad, exponiéndolos al virus del VIH y a la tuberculosis; también se destacan los patrones espaciales basados en categorías de edad que mostraron un riesgo de coinfección generalizado para las edades de 25 a 34 años, seguido de 35 a 44 años (21,22) .…”
Section: Discussionunclassified
“…También se detectaron debilidades con respecto al relleno de los formularios que presentaban información ignorada que obstaculizaba el uso de estos datos y perjudicaba la calidad de la información, ya que la posible utilidad de los datos de notificación de casos proporciona estimaciones sólidas para la amplia estructura espaciotemporal de la coinfección TB-HIV (22) .…”
Section: Discussionunclassified